Anal adenocarcinoma: case report, literature review and comparative survival analysis. Issue 1 (9th July 2021) - Tsay, Cynthia J; Pointer, Thomas; Chandler, Jocelyn B; Nagar, Anil B; Protiva, Petr
Abstract : Introduction: Anal adenocarcinoma is a rare malignancy with a poor prognosis. Methods: We present a case of rare anal adenocarcinoma in a patient with normal screening colonoscopy. Using the Surveillance, Epidemiology and End Result database between 2000 and 2016, we performed survival analysis among individuals>20 years old comparing anal and rectal cancers. Results: Survival analysis showed that anal adenocarcinoma is associated with worse outcomes compared with rectal adenocarcinoma and anal squamous cell carcinoma. Discussion: This case and survival data illustrate the importance of prompt investigation of symptoms irrespective of colorectal cancer screening status with careful attention to examination of the anal area.